2017
DOI: 10.1016/j.jand.2017.06.364
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dietetic Consultations in Primary Health Care: A Systematic Review of Randomized Controlled Trials

Abstract: Dietetic consultations for adults in primary care settings appear to be effective for improvement in diet quality, diabetes outcomes (including blood glucose and glycated haemoglobin values), and weight loss outcomes (eg, changes in weight and waist circumference) and to limit gestational weight gain (Grade II: Fair evidence). Research evaluated in this review does not provide consistent support for the effectiveness of direct dietetic counseling alone in achieving outcomes relating to plasma lipid levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 43 publications
5
136
1
10
Order By: Relevance
“…The results are comparable to those observed in pharmacotherapy studies conducted in high‐risk populations and provide evidence of the effectiveness of dietary therapies for reducing cardiometabolic risk factors. Dietary advice has previously been shown to be effective in the prevention of chronic disease, and dietetic consultation has been shown to elicit improvements in diet quality, weight loss and diabetes outcomes . However, this study is the first to synthesise the effectiveness of dietetic consultation for the management of CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results are comparable to those observed in pharmacotherapy studies conducted in high‐risk populations and provide evidence of the effectiveness of dietary therapies for reducing cardiometabolic risk factors. Dietary advice has previously been shown to be effective in the prevention of chronic disease, and dietetic consultation has been shown to elicit improvements in diet quality, weight loss and diabetes outcomes . However, this study is the first to synthesise the effectiveness of dietetic consultation for the management of CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The current systematic review and meta‐analyses used the same search strategy previously reported for a broader systematic review conducted in 2016 and published in 2017 . RCTs only were included to obtain the highest level of evidence and the lowest likelihood of bias due to their study design and use of a control group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations